2018
DOI: 10.1002/1873-3468.13003
|View full text |Cite
|
Sign up to set email alerts
|

Medium‐chain dehydrogenase/reductase and aldo‐keto reductase scavenge reactive carbonyls in Synechocystis sp. PCC 6803

Abstract: Reactive carbonyls (RCs), which are inevitably produced during respiratory and photosynthetic metabolism, have the potential to cause oxidative damage to photosynthetic organisms. Previously, we proposed a scavenging model for RCs in the cyanobacterium Synechocystis sp. PCC 6803 (S. 6803). In the current study, we constructed mutants deficient in the enzymes medium-chain dehydrogenase/reductase (ΔMDR) and aldo-keto reductase (ΔAKR) to investigate their contributions to RC scavenging in vivo. We found that trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…The large amount of GSH (3.5 mM) in chloroplasts [36] may play an essential role for the detoxification mechanisms of not only ROS but also MG in chloroplasts. Nevertheless, predicted increases in [CO2] and global warming potentially threaten plant growth, and may cause dicarbonyl stress, known as "plant diabetes" [37,38]. The physiological significance of scavenging systems of dicarbonyls in chloroplasts thus provides insight into the acclimation of plants to high [CO2] conditions and will aid in developing future agricultural and biotechnological strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The large amount of GSH (3.5 mM) in chloroplasts [36] may play an essential role for the detoxification mechanisms of not only ROS but also MG in chloroplasts. Nevertheless, predicted increases in [CO2] and global warming potentially threaten plant growth, and may cause dicarbonyl stress, known as "plant diabetes" [37,38]. The physiological significance of scavenging systems of dicarbonyls in chloroplasts thus provides insight into the acclimation of plants to high [CO2] conditions and will aid in developing future agricultural and biotechnological strategies.…”
Section: Discussionmentioning
confidence: 99%
“…However, knocking out these genes also inhibits the organism’s ability to perform photosynthesis. This illustrates the adverse effects of enzymes that participate in multiple pathways, a direct result of their ability to catalyze various compounds [ 12 ]. The current review describes the multifaceted roles of AKRs and their implications in various chronic diseases, as discussed, are largely influenced by their ability to catalyze various compounds, a characteristic that is closely tied to their promiscuous nature.…”
Section: Introductionmentioning
confidence: 99%
“…Several AKRs have been reported to effectively detoxify cytotoxic aldehydes from abiotic-stress-related glycolysis, to improve plant stress resistance. For example, aldo-keto reductase can eliminate reactive carbonyls in Synechocystis [12]; cadmium tolerance was increased in tobacco transformed with IbAKR, which was cloned from sweet potato (Ipomoea batatas) [11]; a novel aldo-keto reductase gene, PpAKR1, from peach (Prunus persica) confers higher tolerance to salt in Arabidopsis [13]; and transgenic tobacco expressing ALDRXV4 from Xerophyta viscosa has increased resistance to drought and salt [14]. However, systematic studies of AKR family with stress resistance in a single species have not been reported.…”
Section: Introductionmentioning
confidence: 99%